Echoes of the public: Public opinion and subnational compliance with European environmental directives - Marie-Thérèse Wilhelm (European Union Politics, 2026)
This study investigates whether public opinion shapes compliance with European environmental directives. Drawing on an original dataset of subnational infringements from 2005 to 2018 across 319 subnational authorities in 20 member states, the analysis links variation in public opinion to compliance using mixed-effects logistic regression models. The results show that subnational public opinion does not exert an independent effect on the likelihood of infringement. Instead, national environmental attitudes emerge as consistently relevant for subnational compliance, with subnational authorities in member states that are less supportive of environmental protection significantly more likely to infringe European Union legislation. Subnational environmental attitudes matter where national environmental support is weak. These findings demonstrate that responsiveness in multilevel governance is conditional upon the interaction between national and subnational public opinion.